Evaluation of Healthcare Workers Presenting to the Outpatient Clinic for COVID-19 Exposure at a University Hospital During Pandemic in Turkey - Aydın, Sümeyye Nur; Can, Günay; Kara Esen, Beril; Pirdal, Betül Zehra; Uygur, Abdulkerim; Sak, Kevser; Erdoğan, Mehmet Sarper; Erginöz, Ethem (Cerrahpaşa Medical Journal, 2023)
Objective: This study aimed to evaluate the exposure status of the healthcare workers in our hospital and to evaluate the factors affecting the exposure levels. In this direction, it is aimed to contribute to the planning of measures that can be taken to reduce the risk exposure rate of healthcare workers. In our hospital, the “Outpatient Clinic for Healthcare Personnel with COVID-19 Exposure” was established in order to monitor the coronavirus disease 2019 exposure risks of healthcare workers. Methods: The data of our study, designed as a retrospective cohort study, were obtained from the follow-up records of 1646 healthcare workers presenting with risk exposure for COVID-19 between March 24, 2020, and January 15, 2021. Risk assessment in healthcare workers according to the “Algorithm for Evaluation of Healthcare Professionals with COVID-19 Exposure” of the Ministry of Health was classified as no risk and low-, medium-, and high-risk exposure. The relationship between the risk levels of the participants, demographic, workplace characteristics, and personal protective equipment use was evaluated. Results: A total of 1646 personnel were applied to our coronavirus disease 2019 exposure personnel outpatient clinic. The majority (90%) of the applicants were not employed in a coronavirus disease 2019-related unit. While 43 (2.6%) personnel were evaluated as risk free, 233 (14.2%) personnel were classified as high-risk exposures, 1012 (61.8%) as medium-risk exposures, and 349 (21.3%) as low-risk exposures. During the follow-up period, 201 (12.2%) of the applicants were found to be coronavirus disease 2019 positive. More coronavirus disease 2019 positivity was seen in personnel with high-risk exposures (P = .003). Conclusion: In our study, hospital-based exposure constitutes the most important source of exposure for healthcare workers. It has been observed that the number of coronavirus disease 2019 exposures and disease development in healthcare workers who do not work in coronavirus disease 2019 units is high. High-risk exposure increases the likelihood of developing coronavirus disease 2019 in healthcare workers. Cite this article as: Aydın SN, Can G, Esen BK, et al. Evaluation of healthcare workers presenting to the outpatient clinic for COVID-19 exposure at a university hospital during pandemic in Turkey. Cerrahpaşa Med J. 2023;47(2):222-228.